THE EFFECT OF SPIN-OFF POLICY ON FINANCING GROWTH IN INDONESIAN ISLAMIC BANKING INDUSTRY - Al Arif, M. Nur Rianto (Al-Ulum, 2015)
The purpose of this paper is to analyze the relationship between spin-off policy on the financing growth of Islamic banking industry in Indonesia. This research used panelÂ  regression with fixed effect. The variable used in this paper is dummy variabel of spin-off, and also included the internal factor of industry such as third party fund, and efficiency ratio (measured by BOPO). Besides the internal factor, this research also included the external factor such as inflation rate, economic growth rate, and interest rate from conventional banking. The result shows that only third part funds and interest rate had an impact on the financing growth in spin-off banks. The spin-off policy doesnât have an impact on the financing growth in spin-off banksÂ -----Tujuan dari penulisan artikel ini ialah untuk menganalisis keterkaitan antara kebijakan pemisahan terhadap pertumbuhan pembiayaan pada industri perbankan syariah di Indonesia. Penelitian ini menggunakan teknik regresi panel dengan model efek tetap. Variabel yang dipergunakan dalam artikel ini ialah variabel dummy pemisahan, serta memasukkan pula faktor internal seperti dana pihak ketiga dan rasio efisiensi yang diukur dari BOPO. Selain itu dimasukkan pula faktor eksternal seperti tingkat inflasi, tingkat pertumbuhan ekonomi, dan tingkat suku bunga dari bank konvensional. Hasil yang ada menunjukkan bahwa hanya dana pihak ketiga dan tingkat bunga yang memiliki pengaruh terhadap pertumbuhan pembiayaan di bank syariah yang pisah. Kebijakan pemisahan tidak memiliki pengaruh terhadap pertumbuhan pembiayaan di bank syariah yang pisah.